High Blood Lead Levels as A Risk Factor of Stunting: A Study of Children in Agricultural Areas - Afandi, Alfan; Suhartono, Suhartono; Budiyono, Budiyono; Margawati, Ani; Kartini, Apoina (Universitas Airlangga, 2025)
Introduction: The prevalence of stunting among student aged children in Indonesia is relatively high (24.5%). Stunting can threaten the quality of human resources one day. Lead exposure, particularly from pesticides, is thought to disrupt children's development and growth. This study aims to demonstrate that high blood lead levels (BLL) is a risk factor of stunting for children who lives in agricultural areas through the intermediate variable, namely interference with growth hormone (IGF-1). Methods: This study used a case-control design, involving 35 cases (children with HAZ scores of less than -2 SD) and 40 controls (children with HAZ scores of more than -1.5 SD). BLL were measured using the atomic absorption spectrophotometer (AAS) method. Meanwhile, insulin-like growth factor-1 (IGF-1) levels using an ELISA kit (R&D Systems). BLL variables and IGF-1 levels were determined using the receiver operating characteristic (ROC) curve. Results and Discussion: High BLL (>20.44 μg/dL) and low IGF-1 levels (<100 ng/ml) were identified risk factors for stunting in children in agricultural areas with odd ratios (OR) od 2.8 (1.1-7.1) and 3.3 (1.3-8.5) respectively. Meanwhile, a negative correlation was discovered between BLL and IGF-1 levels (p = 0.002, r = -0.356). Conclusion: High lead exposure has been proven to be a risk factor for stunting in children in agricultural areas through the process of interference with the growth hormone, namely IGF-1. Efforts to prevent stunting, especially in agricultural areas, need to take into account exposure to environmental toxicants, including lead from pesticides.